Scaling banana bacterial wilt management through single diseased stem removal in the Great Lakes Region - Kikulwe, Enoch; Asindu, Marsy; Ocimati, Walter; Ajambo, Susan; Tinzaara, William; Iradukunda, Francois; Blomme, Guy (Springer, 2022)
Xanthomonas wilt (XW) of banana caused by Xanthomonas vasicola pv. musacearum (Xvm) is an important emerging and non-curable infectious disease which can cause up to 100% yield loss. At the start of the XW epidemic, complete uprooting of diseased mats (CMU) was recommended. There was little adoption of CMU, especially by women farmers, because it was labor-intensive and it sacrificed banana production for up to 2 years. CMU assumed that infection on a single plant would systemically spread to all plants in a mat. However, field experiments showed that Xvm did not spread systemically in a mat and that latent infections occurred. As a result, not all shoots on an infected plant show symptoms. This led to the idea of removing only the visibly infected banana plants, referred to as single diseased stem removal (SDSR). The SDSR package comprises three novations: (1) regularly cutting symptomatic stems at ground level, (2) sterilizing cutting tools with fire, and (3) early male bud removal using a forked stick. The SDSR package was promoted jointly with a set of complementary practices: (i) avoiding infections by browsing animals, (ii) using clean planting materials, (iii) bending leaves at the petiole level when intercropping in infected fields, (iv) training on disease recognition and epidemiology, and (v) demand-specific extension and knowledge sharing. Several approaches that have been used for scaling out XW management technologies are documented in this chapter. This review looks at the process, practices, challenges, lessons learned, and future policy implications associated with scaling of XW management practices.